Blood, guts, and glory : Smoke Jensen, American legend - Johnstone, William W. (Johnstone, William W. Mountain man, 2021)
Revenge of the Mountain Man: Smoke Jensen returns from a cattle buying trip to discover that his wife has been shot by outlaws, and is determined to track down her attackers.